1994
DOI: 10.1042/bj2990253
|View full text |Cite
|
Sign up to set email alerts
|

Expression and protein kinase C-dependent regulation of peptide/H+ co-transport system in the Caco-2 human colon carcinoma cell line

Abstract: The characteristics of the transport of the dipeptide glycylsarcosine were studied in the human colon carcinoma cell line Caco-2 grown as a monolayer on impermeable plastic support. Transport of glycylsarcosine in these cells was found to be Na(+)-independent, but was stimulated by an inwardly directed H+ gradient. This H(+)-dependent transport of glycylsarcosine was inhibited by di- and tri-peptides and also by the beta-lactam antibiotic cephalexin, but was unaffected by the amino acids glycine and leucine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 27 publications
6
91
0
1
Order By: Relevance
“…To our knowledge, this Km is among the lowest Km s reported for hPepT1. For example Gly-Sar, which is the most commonly used PepT1 substrate, has a Km ≥ 1 mM in Caco2-BBE cells (33). Similar results were found in Jurkat cells.…”
Section: Discussionsupporting
confidence: 72%
“…To our knowledge, this Km is among the lowest Km s reported for hPepT1. For example Gly-Sar, which is the most commonly used PepT1 substrate, has a Km ≥ 1 mM in Caco2-BBE cells (33). Similar results were found in Jurkat cells.…”
Section: Discussionsupporting
confidence: 72%
“…16,20,21) It is noted that the activity of hPEPT1 in this cells showed about 35-fold larger than that in Caco-2 cells. [20][21][22] The CHO/hPEPT1 is a powerful tool to study the transport mechanism of hPEPT1. hPEPT1 is an electrogenic H ϩ /dipeptide co-transporter and the substrate of hPEPT1 should cause intracellular acidification.…”
Section: Discussionmentioning
confidence: 99%
“…First, we established stably transfected CHO cells which show high transport activities for various substrates with almost the same K m values as those obtained from those of a model human intestine epithelial cell line, Caco-2. [20][21][22] Thus, this CHO cell line over-expressing hPEPT1 (designated as CHO/hPEPT1) is useful and convenient for transport studies of hPEPT1. In the present study, we then examined the pH-dependency of transport activity by hPEPT1 using CHO/hPEPT1 cells.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, either exposure to two immunosuppressive agents, tacrolimus and cyclosporin A (44), or exposure to thyroid hormone (5) or long-term basolateral stimulation with EGF inhibited the uptake of dipeptides via PEPT1 in Caco-2 cells (44). Moreover, it has been demonstrated that activation of signaling pathways that involve protein kinases C and A changes the kinetic properties of PEPT1 and PEPT2 in intestinal and renal cell lines (13,73). Whether these in vitro observations are of physiological importance in vivo in renal tissues remains to be determined.…”
Section: Regulation Of Expression Level and Transport Activity Of Pepmentioning
confidence: 99%